Essay on financial disclosure papers in Brazilian Soccer Teams - Thais Azzolini Piva; Daniel Luiz Igrejas Andrade Júnior; José Augusto Veiga da Costa Marques (Universidade Salgado de Oliveira, 2020)
This essay aims to analyze papers of financial disclosure of Brazilian football clubs based on the theory of disclosure, seeking to identify unresolved issues and offer opportunities for future research. The benefits associated with disclosure, such as a higher return on investment and a reduction in the cost of capital, are related to the business environment. The essay discusses the existence of two limitations when considering football clubs. The first involves the ability of accounting to fulfill its role of portraying the economic and financial reality of these organizations. The second is the requirement for rational stakeholder expectations. The quantitative articles verified adapt the dissemination and association studies. In qualitative articles, the main issue raised is the low level of disclosure.It appears that the logic that permeates the club's relations with stakeholders is not necessarily rational, considering the existence of a very strong passionate component, which can diminish the relevance of disclosure in this sector. Due to these limitations, it is concluded that clubs do not have the same benefits expected by the disclosure theory, which may justify their low level of disclosure.